Aplikasi Pengujian White Box IBII Online Jugde - Joko Susilo (Jurnal Informatika dan Bisnis, 2014)
The development of information and communication technology assist people in variousaspects of human life. One aspect of those is education. Utilization of information and communicationtechnology in education is useful for users to understand the learning materials quickly and easily.Currently there has been online judge system which used for practice work on the problems ofprogramming. IBII provides a means for students majoring in information systems and informationtechnology for practicing programming capabilities through IBII Online Judge. In IBII Online Judge,there is a problem with the requirements of the use of algorithms and data structures. The purpose ofthis study is to design and create a white-box testing application that can assist test on IBII OnlineJudge. Application of white-box testing IBII Online Judge in this study developed using the Javaprogramming language. The design of white-box testing utilized the theory of lexical analysis withknowledge of algorithms and data structures. This study was developed using the methods of systemsdevelopment life cycle (SDLC) waterfall model. The design of the system used in this study describedas an object-oriented by using Unified Modeling Language (UML) such as use case diagram, classdiagrams, sequence diagrams and activity diagrams. The results of this study were white-box testingapplication that can assist test on IBII Online Judge. The conclusions of this research is theapplication of white-box testing IBII Online Judge useful to perform testing on the user’s submittedsource code to the requirements of IBII Online Judge problem in the use of algorithms and datastructures.